Psychological Consequences of Cosmetic Botox Therapy - Gronowicz, Gabriela; Warunek, Aleksandra; Wanat, Joanna; Dzikowska, Izabela; Homa, Wojciech; Siejka, Agata; Stefaniak, Daria; Zielińska, Weronika; Chról, Michał (Quality in Sport, 2025)
The face plays an essential role in social communication, both through its permanent features, which indicate age, and through dynamic changes in facial expressions, which convey emotional states and intentions. There is a bidirectional relationship between facial expressions and mood—emotions influence facial expressions, while facial expressions, in turn, impact well-being. Mirror neurons cause observing another person's facial expressions to evoke similar feelings in the observer. When injected locally, botulinum toxin blocks cholinergic transmission, leading to muscle relaxation. By smoothing out facial wrinkles, the face becomes a less expressive indicator of emotions and mood. Botox is commonly used to reduce wrinkles caused by the contraction of the corrugator muscle, which gives the face a sad or stern appearance. Consequently, this treatment can lead to an improved mood. For this reason, Botox is being explored as a potential method of antidepressant therapy.